Evaluation of the antimicrobial properties of eel skin mucus from monopterus albus against selected oral pathogens and identification of the anti-oral bioactive compounds using LC-QTOF-MS - Hilles, A. R.; Mahmood, Syed; Mohd Arifin, Kaderi; Ridzwan, Hashim (Faculty of Biotechnology and Food Sciences, 2019)
Despite great achievements in the oral health of populations globally, oral health problems remain in many communities all over the world, thus our study aimed to evaluate the antimicrobial activity of Monopterus albus skin mucus against selected oral pathogens. Monopterus albus is Asian swamp eel with elongated body like snakes. Their skin covered with a thick layer of mucus. They are usually found as a sluggish in the stagnant waters as it has a weak swimming behavior. Although eels are capable of quick movements, but they tend to be lethargic and they rely on stealth swimming movements to capture their prey such as shrimp, frogs and other small fishes. With regard to this matter, aqueous and methanol extracts were prepared to test antimicrobial activities against selected oral pathogens; Gram-positive bacteria i.e. Enterococcus faecalis, Streptococcus pyogenes, Streptococcus mutans, Gram-negative bacteria which are Klebsiella pneumoniae, Pseudomona aeruginosa and fungus pathogens i.e. Candida albicans. The antimicrobial activities were determined by inhibition percentage. The results showed a dramatic decrease in the oral pathogens treated with eel skin mucus methanol extract higher than the aqueous extract. Enterococcus faecalis showed the highest activity while Candida albicans showed the lowest activity. After in-vitro evaluation for eel skin mucus activities, identification study using liquid chromatography-quadrupole-time-offlight mass spectrometry (LC-QTOF-MS) was performed to investigate the compound responsible for the anti-oral pathogens activities, the results showed the presence of salvianolic acid G which strongly corelated with the antimicrobial activity against selected oral pathogens. Results were statistically significant with p < 0.001. In conclusion, the present study revealed that eel skin mucus can be considered as promising source for anti-oral pathogens activities.